2019
DOI: 10.1161/hypertensionaha.118.12300
|View full text |Cite
|
Sign up to set email alerts
|

EGFR (Epidermal Growth Factor Receptor) Signaling and the Mitochondria Regulate sFlt-1 (Soluble FMS-Like Tyrosine Kinase-1) Secretion

Abstract: Preeclampsia is a hypertensive disorder of pregnancy characterized by maternal endothelial dysfunction and end-organ damage. The antiangiogenic factor, sFlt-1 (soluble FMS-like tyrosine kinase-1) has been strongly implicated in the pathogenesis of preeclampsia. sFlt-1 is secreted into the maternal circulation where it antagonizes VEGF (vascular endothelial growth factor) and ultimately disrupts vascular homeostasis. However, the upstream mechanisms regulating release of sFlt-1 are poorly characterized. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 58 publications
1
35
0
1
Order By: Relevance
“…The present study aimed to determine the mechanism underlying incomplete trophoblastic invasion in PE. However, endothelial dysfunction is also one of the major causes of PE (4), yet this was not explored in our study this paper; thus, this should be investigated in the future.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study aimed to determine the mechanism underlying incomplete trophoblastic invasion in PE. However, endothelial dysfunction is also one of the major causes of PE (4), yet this was not explored in our study this paper; thus, this should be investigated in the future.…”
Section: Discussionmentioning
confidence: 93%
“…The pathogenesis of PE is not fully understood; thus, as an effective treatment for PE, pregnancies may be terminated. At present, PE is considered to be associated with dysfunction of the placenta (3), endothelial dysfunction (4) and abnormal increases in the apoptosis of trophoblasts (5). Of note, increased migration and invasion of trophoblastic cells, and decreased apoptosis have been hypothesized as potential therapeutic strategies for the treatment of PE; however, further investigation is required.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, insulin resistance and endothelial dysfunction represent early events in individuals at high risk of developing cardiovascular disease later in life (35). The Epidermal Growth Factor Receptor (EGFR) signaling, which is related to fetal growth restriction, gestational trophoblastic diseases and PE was found significantly enriched in the present study (36). Hastie et al (2019) showed simultaneous targeting of both EGFR signaling and mitochondrial function using a combination of esomeprazole and metformin results in additive reductions in sFlt-1 production suggesting their use as preventive therapeutic interventions for PE (36).…”
Section: Discussionmentioning
confidence: 60%
“…AKT acts on a variety of targets involved in many cellular processes, such as metabolism, cell cycle, survival, and differentiation [50][51][52]. It has been demonstrated that placental pathology in preeclampsia and retarded fetuses is related to changes in the expression pattern of EGFR [53], and the antiangiogenic factor, sFlt-1 (soluble FMS-like tyrosine kinase-1), has been strongly implicated in the pathogenesis of preeclampsia and was mediated by EGFR signaling [54].…”
Section: Discussionmentioning
confidence: 99%